2007
DOI: 10.1093/humrep/dem077
|View full text |Cite
|
Sign up to set email alerts
|

Insulin dependant diabetes mellitus: implications for male reproductive function

Abstract: Diabetes is associated with increased sperm nuclear and mtDNA damage that may impair the reproductive capability of these men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
323
2
13

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 440 publications
(356 citation statements)
references
References 89 publications
18
323
2
13
Order By: Relevance
“…Pathophysiological dysfunctions in diabetes is associated with oxidative stress which is likely to contribute abnormalities in sperm nuclear DNA. The earlier study has reported an increase in sperm nuclear abnormalities in diabetic patients [2]. Since human studies have ethical and technical limitations to find an exact relationship between blood glucose level and sperm chromatin integrity, we assessed sperm DNA damage in controlled hyperglycemic condition for a period two spermatogenesis cycles and then correlated with blood glucose level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathophysiological dysfunctions in diabetes is associated with oxidative stress which is likely to contribute abnormalities in sperm nuclear DNA. The earlier study has reported an increase in sperm nuclear abnormalities in diabetic patients [2]. Since human studies have ethical and technical limitations to find an exact relationship between blood glucose level and sperm chromatin integrity, we assessed sperm DNA damage in controlled hyperglycemic condition for a period two spermatogenesis cycles and then correlated with blood glucose level.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have shown that patients with DM have diminished sperm quality which is possibly due to endocrine dysfunction as the alteration in testosterone level in DM is associated with steroidogenic defect in Leydig cells [1][2][3]. In addition, it has been shown that diabetic men have a significantly higher percentage of spermatozoa with nuclear DNA damage [2] possibly due to oxidative stress. Sperm DNA integrity is essential for accurate transmission of genetic information to the offspring.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, translocation is most common chromosomal abnormality. A study showed that the frequency of chromosomal translocations was 2.1% in infertile men [46]. Chromosomal translocations can be of many typesRobertsonian translocation, reciprocal translocation and these account for 10% of the causes of male infertility [47].…”
Section: Molecular Insight Into Male Infertilitymentioning
confidence: 99%
“…Vignon et al (1990) have previous reported a significant increase in sperm concentration in TIDM patients, while Garcia-Diez (1991) has reported a significant decrease in sperm count, motility and percentage of spermatozoa with normal morphology. However, Agbaje et al (2007) have found an insignificant increase in sperm concentration and total sperm output with an insignificant decrease in sperm motility, and normal sperm morphology. The authors suggested Leydig cell hyperplasia as the cause of the enhanced spermatogenesis, though with poor motility.…”
Section: Effect Of Diabetes Mellitus On Spermatogenesismentioning
confidence: 95%